Channel Allocation Schemes for Permanent user Channel Assignment in Wireless Cellular Networks. Issue 2 (3rd March 2016) - Usman, Muhammad Rehan; Shin, Soo Young
ABSTRACT: In this paper, two different models for permanent user channel assignment, based on Markov chain, are proposed for wireless cellular networks. Both models include channels for calling, handover, and permanent assignment. Models in this paper provide comparison of the blocking probabilities and handover failure probabilities after introducing the permanent user channel assignment, further permanent user channel blocking probability is also derived. Based on the blocking probability results, risk analysis to predict the blocked channels is provided at the end of this paper using the @Risk tool. The simulation results are provided in two parts, i.e. (1) the probability curves against the number of assigned channels are shown and (2) the results using @Risk tool for the risk analysis are shown.